Systemic autoimmune diseases co-existing with chronic hepatitis C virus infection (the HISPAMEC Registry): patterns of clinical and immunological expression in 180 cases (2005)
Objectives. To describe the clinical and immunologic characteristics of a large series of patients with systemic autoimmune diseases (SAD) associated with chronic hepatitis C virus (HCV) infection. Methods. We analysed 180 patients diagnosed with SAD and chronic HCV infection seen consecutively at our centres during the last 10?years. The clinical and immunological patterns of disease expression were compared with 180 SAD?matched patients without chronic HCV infection. Results. A total of 180 HCV patients fulfilled the classification criteria for the following SAD: Sjögren's syndrome (n ?=?77), systemic lupus erythematosus (n ?=?43), rheumatoid arthritis (n ?=?14), antiphospholipid syndrome (n ?=?14), polyarteritis nodosa (n ?=?8) and other SAD (n ?=?24). One hundred and thirty (72%) patients were female and 50 (28%) male, with a mean age at SAD diagnosis of 50?years. The main immunologic features were antinuclear antibodies in 69% of patients, cryoglobulinaemia in 62%, hypocomplementaemia in 56% and rheumatoid factor (RF) in 56%. Compared with the SAD?matched HCV?negative group, SAD?HCV patients presented a lower prevalence of females (P ?=?0.016), an older age at SAD diagnosis (P ?=?0.039) and a higher prevalence of vasculitis (P ?<?0.001) and neoplasia (P ?<?0.001). Immunologically, SAD?HCV patients presented a lower prevalence of antinuclear (P ?=?0.036), anti?extractable nuclear antigen (P ?=?0.038) and anti?DNA (P ?=?0.005) antibodies, and a higher frequency of RF (P ?=?0.003), hypocomplementaemia (P ?<?0.001) and cryoglobulins (P ?<?0.001). Conclusions. In comparison with an SAD?matched HCV?negative population, SAD?HCV patients were older and more likely to be male, with a higher frequency of vasculitis, cryoglobulinaemia and neoplasia. This complex pattern of disease expression is generated by a chronic viral infection that induces both liver and autoimmune disease.